Assessment of proliferative activity using the MIB1 antibody help to distinguish polymorphous low grade adenocarcinoma from adenoid cystic carcinoma of salivary glands - Skálová, A; Simpson, R H; Lehtonen, H; Leivo, I (Pathology, research and practice, 1997)
Salivary polymorphous low grade adenocarcinoma (PLGA) and adenoid cystic carcinoma (AdCC) bear a superficial histological and immunophenotypic resemblance to each other, but can usually be separated by conventional microscopic examination. However, this is not always so, such as with PLGAs displaying plentiful cribriform structures, and when only limited tissue from small biopsies is available for study. Twenty-one cases of PLGA and 20 cases of AdCC from the surgical pathology files in Plzen, Exeter and Helsinki were incubated with the MIB1 antibody using the supersensitive avidin-biotin peroxidase technique after microwave pretreatment. The antibody recognizes the cell cycle associated antigen Ki-67 on routinely processed formalin-fixed paraffin-embedded tissues. The percentage of positively stained tumor cell nuclei constituted the MIB1 index. It was found that the PLGAs had a mean MIB1 index of 2.4% (range 0.2-6.4), while the AdCCs had a mean value of 21.4% (range 11.3-56.7). Within the PLGA group, the 12 tumors which did not form micropapillae had a somewhat lower mean MIB1 index (1.4%) than those nine in which such structures constituted a significant but minor component (3.4%). These results indicate that the MIB1 index was significantly higher in the AdCCs than the PLGAs and that the figures showed no overlap zone. We conclude, therefore, that immunohistochemical staining with the MIB1 antibody appears to be a potentially useful supplementary diagnostic tool in differentiating difficult cases of PLGA from AdCC.
Keywords: Adenocarcinoma; adenoidně cystický karcinom; fatální výsledek; Cell Division; Humans; lidé středního věku; Carcinoma, Adenoid Cystic; dítě; Child; Female; Aged; Salivary Gland Neoplasms; dospělí; počet buněk; senioři; lidé; Immunohistochemistry; Ki-67 Antigen; nádory slinných žláz; imunohistochemie; antigen Ki-67; Adult; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Aged, 80 and over; senioři nad 80 let; adenokarcinom; retrospektivní studie; Fatal Outcome; mužské pohlaví; Cell Count; následné studie; buněčné dělení